The interaction between the community food environment and cooking skills in association with diet-related outcomes in Dutch adults - Noreen Z Siddiqui; Maria GM Pinho; Femke Rutters; Joline WJ Beulens; Joreintje D Mackenbach (Cambridge University Press, 2023)
Abstract Objective: We examined whether associations between the food environment, frequency of home cooking, diet quality and BMI were modified by the level of cooking skills. Design: Cross-sectional study using linear and modified Poisson regression models adjusted for age, sex, energy intake, education, income, household size and urbanisation. The frequency of home cooking was categorised into <6 and 6-7 d. Diet quality was based on a validated Dutch healthy diet index (0-150 points). Count of restaurants and food stores were determined by their count in a 1000m buffer around home and work. Cooking skills (score 1-5) were assessed using a validated questionnaire and added as interaction term. Setting: The Netherlands. Participants: 1461 adults aged 18-65 years. Results: Count of restaurants and food stores were not associated with the frequency of home cooking. A 10-unit higher count of food stores was associated with a higher diet quality (β: 0·58 (95 % CI (0·04, 1·12)), and a 10-unit higher count of restaurants was associated with a lower BMI kg/m2 (β: −0·02 (95 % CI (-0·04, −0·004)). Better cooking skills were associated with a higher likelihood of cooking 6-7 d compared with <6 d (risk ratio: 1·24 (95 % CI (1·16, 1·31)) and a higher diet quality (β: 4·45 (95 % CI (3·27, 5·63)) but not with BMI. We observed no interaction between the food environment and cooking skills (P-for-interaction > 0·1). Conclusions: Exposure to food stores was associated with a higher diet quality and exposure to restaurants with a lower BMI. Better cooking skills were associated with a higher frequency of home cooking and better diet quality but did not modify associations with the food environment. Future studies should explore different approaches to understand how individuals interact with their food environment.